Argumen Al-Qur’an Tentang Paradigma Ekopedagogi - Adudin Alijaya; Muhammad Hariyadi (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2019)
Conclution of the research states that ecopedagogy is a public educational movements of human responsibility in environmental conservation. It’s conducted by combining all environmental conservation paradigms, analyzing its deficiency and advantages, thus, associating it with Qur’anic environmental themes. Some of the paradigms is analyzed in the effort to increase ecological concern are: anthropocentric, biocentric, ecocentric, zoocentric, ecophenomenology, androcentric, conservation and ecofeminism. These paradigms all get reinforced arguments from the Qur’an which outline that all living things and all their phonemes have relations with each other and need to be made in such harmony. But the Qur’an also emphasizes the other side that must be considered as a form of environmental balance and ethics. So by using the ecopedagogy method that combines eight methods in nature conservation, the best public education method has been carried out in order to embody nature conservation. The methodology used in this study is a qualitative method that is integrated with the thematic method (mawdhu’î), while the data used in this study were obtained through library research with three stages of research, namely the stages of description, comparison and analysis, which ultimately obtained conclusions in accordance with the formulation and research objectives.